2006
DOI: 10.1180/0026461067010314
|View full text |Cite
|
Sign up to set email alerts
|

Crystal symmetry and chemical composition of yukonite: TEM study of specimens collected from Nalychevskie hot springs, Kamchatka, Russia and from Venus Mine, Yukon Territory, Canada

Abstract: Yukonite, a rare arsenic-bearing hydrous mineral, the crystal symmetry and variety in chemical composition of which have so far been insufficiently studied, has been found in the modern deposit of Nalychevskie hot springs in Central Kamchatka, Russia. This is the first finding of yukonite in Eastern Eurasia and Siberia. Yukonite specimens from Nalychevskie hot springs and from Venus Mine in Yukon Territory, Canada, have been investigated using an analytical transmission electron microscope (TEM). Yukonite is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 4 publications
5
14
0
Order By: Relevance
“…In the results section, new unit cell parameters, a = 11.341(6) Å and c = 11.57(2) Å in a hexagonal cell, were proposed for wallkilldellite-(Fe) from the electron diffraction pattern in TEM observation. When the index of wallkilldellite-(Fe) is applied to yukonite, the unit cell parameters can be written as a = 11.349(6) Å and c = 14.7(2) Å, in good agreement with Nishikawa et al (2006) and Garavelli et al (2010). Comparing the unit cells, yukonite has longer periodicity than wallkilldellite-(Fe) along the c axis, but it is nearly iden- Table 2.…”
Section: Wallkilldellite-(fe)supporting
confidence: 69%
See 2 more Smart Citations
“…In the results section, new unit cell parameters, a = 11.341(6) Å and c = 11.57(2) Å in a hexagonal cell, were proposed for wallkilldellite-(Fe) from the electron diffraction pattern in TEM observation. When the index of wallkilldellite-(Fe) is applied to yukonite, the unit cell parameters can be written as a = 11.349(6) Å and c = 14.7(2) Å, in good agreement with Nishikawa et al (2006) and Garavelli et al (2010). Comparing the unit cells, yukonite has longer periodicity than wallkilldellite-(Fe) along the c axis, but it is nearly iden- Table 2.…”
Section: Wallkilldellite-(fe)supporting
confidence: 69%
“…The chemical composition and X-ray powder diffraction pattern of this type material was later reexamined by Jambor (1966). Yukonite has been reported from several localities other than the type locality (Dunn, 1982;Ross and Post, 1997;Pieczka et al, 1998;Nishikawa et al, 2006;Garavelli et al, 2009). It occurs mostly as a red to yellowish-brown waxy gel-like material or as compact masses of the same color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jambor later (1966) re-examined the yukonite formula and proposed the following: Ca 6 Fe 16 (AsO 4 ) 10 (OH) 30 Á 23H 2 O. The occurrence of yukonite since then has been reported among others, in the Sterling Hill mine, Ogdensburg, New Jersey, USA by Dunn (1982), in Saalfeld, Thuringen, Germany by Ross and Post (1997), Redziny, Sudetes, Poland by Pieczka et al (1998), Nishikawa et al (2006) in Kamchatka, Russia and very recently by Garavelli et al (2009) in Grotta della Monaca, Italy. Yukonite has been reported to occur most often as intensively fractured, gel-like aggregates or dark brownish in hand-specimens; in smaller fragments it is purple reddish and slightly translucent.…”
Section: Introductionmentioning
confidence: 94%
“…From this analysis as shown above, it was confirmed that this structure have water molecules, hydroxyl groups that were found to still exist even after heating the sample to > 600 °C (Figure 1). Therefore, based on all this vibrational evidence our preference for a "new"(similar to work by Moore & Ito, 1974) (Tyrrell & Graham, 1913;Jambor 1966;Ross & Post 1997;Pieczka et al, 1998;Paktunc et al, 2003Paktunc et al, , 2004Nishikawa et al, 2006;Becze and Demopoulos 2007;Walker et al, 2009;Garavelli et al, 2009). Finally, in this work it was observed that for arseniosiderite, and additional arsenate IR and Raman active vibrations occurred ~ 900 cm -1 indicative of protonated arsenate groups.…”
Section: Samplementioning
confidence: 99%